Oviposition of Quesada gigas (Hemiptera: Cicadidae) in coffee plants - Decaro Junior, Sergio T. [UNESP]; Martinelli, Nilza Maria [UNESP]; Maccagnan, Douglas H. B.; Ribeiro, Eduardo S. D. B. P. [UNESP] (Soc Colombiana Entomologia-socolen, 2012)
Branches of coffee-plant were collected in Sao Sebastiao do Paraiso County, Minas Gerais State, at the Experimental Station of the Agricultural Research Company (Empresa de Pesquisa Agropecuaria de Minas Gerais - EPAMIG), with the aim of studying various aspects of oviposition by Quesada gigas (Hemiptera: Cicadidae). The number of branches with Q. gigas egg nests was analyzed, as well as the number of nests per branch, the eggs per nest and the diameter of the egg nest location on the branch. The preference for oviposition either on alive or dry branches and the size of the egg were assessed. Egg-laying occurred only on dry branches. The mean of the branch diameter on which the egg nests occurred was 2.5 +/- 0.53 mm. The number of eggs per nest averaged 13.2 +/- 4.9, and the number of egg nests per branch was 2.2 +/- 1.74. The eggs were 1.9 +/- 0.08 mm long by 0.5 +/- 0.04 mm wide. The largest diameters of the branches containing egg nests were found on the upper third of the trees, as well as the greatest amount of branches with egg nests, of egg nests per branch and of eggs per nest. The correlation relationship between all of the experiment variables was positive.

Se realizaron colectas de ramas de plantas de café en el municipio de Sao Sebastiao do Paraíso, estado de Minas Gerais, en la Estación Experimental de la Empresa de Investigación Agropecuaria (Empresa de Pesquisa Agropecuaria de Minas Gerais - EPAMIG), con el objetivo de estudiar la oviposición de Quesada gigas (Hemiptera: Cicadidae). Se analizaron el número de ramas con postura de Q. gigas, postura por rama, huevos por postura y diámetro del sitio de postura de la rama. Se evaluó la preferencia por oviposición en las ramas verdes o secas y las dimensiones de los huevos. Las posturas solo ocurrieron en las ramas secas. El promedio del diámetro de la rama en que las posturas ocurrieron fue 2,5 ± 0,53 mm. El número de huevos por postura fue em promedio 13,2 ± 4,9, y el número de posturas por rama fue de 2,2 ± 1,74. El huevo tiene dimensiones de 1,9 ± 0,08 mm de longitud por 0,5 ± 0,04 mm de ancho. Los mayores diámetros de ramas que contienen posturas, mayor número de ramas con postura, mayor número de posturas por rama y mayor número de huevos por postura se encontraron en el tercio superior. La correlación entre las variables del experimento fueron positivas.
Oviposición de Quesada gigas (Hemiptera: Cicadidae) en plantas de café
Keywords: Cicadoidea; Cicada; Coffea arabica; Dry branches; Egg nest